Pelatihan Dan Manajemen Potensi Desa Menggunakan Sistem Informasi Desa dan Mini E-Commerce Sebagai Upaya Peningkatan Ekonomi Masyarakat di Desa Motihelumo - Setiawan, Edi; Zakaria, Alfian; Padiku, Indhitya R. (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
The goal to be achieved in this Maritime Thematic KKN activity is the creation of an independent village that is able to manage and map every potential that exists in the village by utilizing information technology, as well as creating wider space for business actors with mini e-commerce to promote business / potential owned for the sake of improving the economy of rural communities in general. With specific targets, namely (1) developing and implementing technology that is directly useful in the community, (2) realizing business management and marketing potential in the village by utilizing mini e -commerce. This Maritime Thematic KKN activity method is a workshop method in the form of training and mentoring to the community through intensive training on the use of village information systems with mini e-commerce so that all targets and outputs are expected through the implementation of this Maritime Thematic KKN activity. increase the economic potential of the community.